1999
DOI: 10.3354/meps187147
|View full text |Cite
|
Sign up to set email alerts
|

Food sources of an infaunal suspension-feeding bivalve Cerastoderma edule in a muddy sandflat of Marennes-Oléron Bay, as determined by analyses of carbon and nitrogen stable isotopes

Abstract: Stable carbon and nitrogen isotope ratios were used to define the trophic base of the infaunal suspension-feeding bivalve Cerastoderma edule (L.) living on an intertidal muddy sandflat in Marennes-Oleron Bay, France. Suspended particulate organic matter (POM) collected from adjacent marine channels had a mean 6I3C value of -22 2 * 1.1 %O (n = 19). Benthic primary producers on Ronceles-Bains tidal flats had 613C values distinct from that of the POM: microphytobenthos (-16.0 * 0.6%).the macroalgae Enteromorpha c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
81
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 27 publications
19
81
2
1
Order By: Relevance
“…The ingestion of macroalgal dissolved organic matter aggregates and associated bacteria (such as in the scallop Argopecten irradians, see Alber & Valiela 1995) could explain the depleted 8 13 C (characteristic of the macroalgal substrate) and 8 34 S (from bacterial sulphide production) signatures of A. stutchburyi. No suspension-feeding bivalve has yet been shown to ingest seagrass material in the field (Stephenson et al 1986;Kang 1999;Kharlamenko et al 2001), which reinforces the notion that seagrass material becomes available to consumers (e.g., grazers and deposit feeders) through its presence as detritus in the sediments (Vizzini et al 2002b). Amongst the invertebrates considered in this study, ingestion of live Z. capricorni tissue has only been documented for the crab M. hirtipes (Woods & Schiel 1997).…”
Section: Nosupporting
confidence: 52%
“…The ingestion of macroalgal dissolved organic matter aggregates and associated bacteria (such as in the scallop Argopecten irradians, see Alber & Valiela 1995) could explain the depleted 8 13 C (characteristic of the macroalgal substrate) and 8 34 S (from bacterial sulphide production) signatures of A. stutchburyi. No suspension-feeding bivalve has yet been shown to ingest seagrass material in the field (Stephenson et al 1986;Kang 1999;Kharlamenko et al 2001), which reinforces the notion that seagrass material becomes available to consumers (e.g., grazers and deposit feeders) through its presence as detritus in the sediments (Vizzini et al 2002b). Amongst the invertebrates considered in this study, ingestion of live Z. capricorni tissue has only been documented for the crab M. hirtipes (Woods & Schiel 1997).…”
Section: Nosupporting
confidence: 52%
“…We can just say that phytoplankton is not the only resource being used by the scallops. One can also argue that microphytobenthos can be the main source of P. maximus diet as its classical average value is -16‰ (Kang et al, 1999). Nevertheless, this hypothesis can be ruled out as the main as we sampled scallops at 30m depth.…”
Section: Discussionmentioning
confidence: 83%
“…So, using classical tissue enrichment factors and average stable isotope values of muscle (δ 13 C = -15.2‰; δ 15 N = 9.4‰) and whole body (δ 13 C and δ 15 N calculated whole body = -16.6 and 8.5‰ respectively), one should expect the isotopic ratios of the filter-feeder's diet to be about -16.2 (muscle) or -17.6‰ A classical mixing model (see Raikow and Hamilton, 2001) could predict that Pecten maximus consume a mixed diet with a minority of phytoplankton, or conversely, that it consume mainly phytoplankton together with a small amount of another food of very enriched δ 13 C value. As in mussels, the P. maximus diet might include dissolved organic carbon (Roditi et al, 2000), deposit material (Raikow and Hamilton, 2001), benthic algae, microheterotrophs and bacteria (Kang et al, 1999;Kreeger and Newell, 2001;Nichols and Garling, 2000). As we did not have stable isotope values of these potential food sources in the Bay of Brest, (but only overall POM) we cannot evaluate the scallop's diet in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with Lopez and Kofoed (1980) and Harkey et al (1994) who found that both filter and deposit feeders are able to select particles of a certain size. Kang et al (1999) suggested that there are 2 major sources of organic matter assimilated by bivalves, phytoplankton and suspended particulate organic matter (POM). They found that adult bivalves exhibited higher dependence on POM variability, while juveniles are more closely linked to phytoplankton.…”
Section: Discussionmentioning
confidence: 99%